2017
DOI: 10.3329/bjms.v16i1.31138
|View full text |Cite
|
Sign up to set email alerts
|

Role of subcutaneous closed vacuum drain in preventing surgical site infection in emergency surgery for perforative peritonitis: A randomized control study

Abstract: Abstract:Objective: The aim of our study was to evaluate whether insertion of a subcutaneous closed suction vacuum drain at incisional surgical site reduces the incidence of surgical site infection (SSI) in post operative cases of exploratory laparotomy for perforative peritonitis. Methods: An institutional based randomized control study was performed with two hundred patients each included in the study (with drain) and control (without drain) group. Both groups were statistically similar in terms of various v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…6 Kumar et al posted that the SSI incidence was 16% in patients with subcutaneous drain and 58% in patients without subcutaneous drain in patients undergoing emergency surgery for perforative peritonitis. 7 Vaghani et al in their study on ileal perforation cases found SSI rate of 25% in patients with subcutaneous drain and 57.7% in patients without subcutaneous drain. 8 El-Badry et al in his study on emergency laparotomy cases found the SSI rate to be 11% in patients with subcutaneous drain and 44% in patients without subcutaneous drain.…”
Section: Discussionmentioning
confidence: 92%
“…6 Kumar et al posted that the SSI incidence was 16% in patients with subcutaneous drain and 58% in patients without subcutaneous drain in patients undergoing emergency surgery for perforative peritonitis. 7 Vaghani et al in their study on ileal perforation cases found SSI rate of 25% in patients with subcutaneous drain and 57.7% in patients without subcutaneous drain. 8 El-Badry et al in his study on emergency laparotomy cases found the SSI rate to be 11% in patients with subcutaneous drain and 44% in patients without subcutaneous drain.…”
Section: Discussionmentioning
confidence: 92%
“…However Gupta and Kumar [19] , found that 37% patients developed surgical site infection post emergency abdominal surgery. Kumar et al [22] also found 37% patients developed surgical site infection in laparotomy for perforated peritonitis. Surgical site infection developed in15.5% of duodenal ulcer perforation, 16.7% of gastric ulcer perforation, 23.5% of traumatic small bowel perforation, 37.5% of ileal perforation and 36% of burst appendix.…”
Section: Discussionmentioning
confidence: 92%
“…Gupta and Kumar [19] , supported this result that 72% of patients were male and 38% were female. Kumar et al [22] found 58.0% of patients were male and 42.0% of cases were female. The most common perforation peritonitis was duodenal ulcer perforation (28.9%), followed by burst appendix (27.8%), traumatic small bowel perforation (18.9%), ileal perforation (17.5%) and gastric ulcer perforation (6.7%).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations